(untitled) (NAU Journal of Technology and Vocational Education, 2025)
Artificial Intelligence (AI) continues to create new paths in the profession of teaching globally, strengthening the routes required to regulate tasks, enhance efficiency, and improve the instructional process. The main objective of this study was to unravel the perception of lecturers on the pressing obstacles of applying AI for effective delivery of business education courses in Delta State University, Abraka, Nigeria. In order to attain the objectives of the study, two research questions were raised to guide the study and two null hypotheses were formulated at 0.05 level of significance. The population of the study comprised of forty-three (43) business education lecturers in the Department of Business Education, Delta State University, Abraka. There was no sample for the study as the population size was small and manageable. A structured questionnaire titled: Lecturers’ Perception on Emerging Challenges of Using Artificial Intelligence Tools for Successful Instruction of Business Education Courses (LPECUAITSIBECQ) was used for data collection. The research instrument was validated by three experts in the Department of Business Education, Delta State, University, Abraka. The test re-test reliability method was adopted by the study to ascertain the consistency of the research instrument which yielded a co-efficient value of 0.81 and 0.77 for the two clusters. The researcher along with two other trained research assistants administered the questionnaires to the respondents. Data collected were analyzed using descriptive statistics such as mean and standard deviation to analyze the research questions raised in the study and to ascertain the homogeneity of the respondents’ opinions or otherwise. The independent t-test was adopted by the study to test the hypotheses at 0.05 level of significance. Based on the findings of the study, it was recommended amongst others: that lecturers should regularly and periodically enroll in in-service training on the application of AI-driven technologies for effective delivery of business education courses.